Effect of Synthesis Condition on Degree of Deacetylation of Chitosan from Shrimp Waste for Smart Film Applications - Reza, Muhammad; Gailani, Jauhairiyah; Susanti, Tria; Zuhro, Syarifa Aminatuz; Sjaifullah, Achmad; Busroni, Busroni; Rahmawati, Istiqomah (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2024)
Shrimp is an Indonesian’s export commodity with high economic value increasing every year. Usually, shrimps are exported in the form of frozen shrimp without shells, heads, tails, and entrails. It resulted in the accumulation of shrimp waste leading to the increasing environmental pollution. Shrimp waste contains high contents of chitin which can be processed to a chitosan owing several benefits. The purpose of this study is to determine the optimum condition of the synthesis of chitosan from chitin isolated by the autolysis method. The deproteination was carried out by soaking the shrimp waste in an acidic solution (pH 2 – 3) for 10 d. The demineralization process was done by reacting the deproteinated solids in a hydrochloric acid solution at pH 0 – 1 for 24 h. Parameters varied in this study time (1 – 3 h), chitin to NaOH ratio (1:10 – 1:30 (w/v)), and temperature (60 – 120℃). The higher all parameters used, the higher the obtained degree of deacetylation (DD) which is in the range of 18.35±1.13 to 48.6±0.51%. On the other hand, the obtained yield decreased from 50.66±1.98% to 47.78±0.81%. The optimum condition was obtained at a synthesis temperature of 120℃, chitin to NaOH ratio of 1:20 g/mL, and time of 3 h producing chitosan with DD of 54.25 ± 2.27%, and yield of 47.7 ± 0.65%. Chitosan synthesized using optimum conditions produced a relatively homogeneous thin film. Polyaniline was then introduced to the film to obtain a smart film prototype. This smart film was able to detect the pH changes proven by the change in its color. The smart film also could be potentially used as a “smart pack” for detecting product decay which releases ammonia gas.